Factors associated to the overweight in adults assisted by a family health unit - Raildo da Silva Coqueiro; Adriana Alves Nery; Zoraide Vieira Cruz; Cloud Kennedy Couto de Sá (Universidade Federal de Santa Catarina, 2008)
http://dx.doi.org/10.5007/1980-0037.2008v10n2p149 The objective of this study was to investigate the factors associated with overweight in adults and the frequencies of these factors. The sample comprised 101 adults, all aged ≥ 18 years, 75 (74.0%) females and 26 (26.0%) males, registered at a Family Health Center (FHC) in the town of Jequié, and distributed proportionally throughout the FHC's seven sub-areas. Patients were defined as overweight if their body mass index (BMI) was ≥ 25kg/m². The proportion of overweight people was calculated for the whole sample and for each of the associated variables (age, sex, occupation, educational level, number of meals per day, smoking, alcoholism, arterial hypertension, diabetes, dyslipidemia and habitual level of physical activity). The chi-square test was applied to test associations between the variables and the proportion of overweight to a significance level of 5% (p ≤ 0.05). the overall frequency of overweight was 28.0%, and this was more prevalent only among individuals who do not consume alcoholic beverages, although the comparison between those with and without hypertension was borderline (p = 0.052). The results of this study suggest a need for further investigation into the effect of alcoholic beverages on the nutritional status of adults and for implementation of nutritional vigilance strategies at this FHC, with special attention given to hypertense patients.